PENCIPTAAN KOMPOSISI MISINDHANDHANG BERBASIS BENTUK GENDING DAN SEKAR MACAPAT - Sutrisni; asep saepudin - (TAMUMATRA, 2025)
This writing aims to provide an overview of Misindhandhang's compositional work in the realm of Javanese karawitan tradition. Compositional works can create new works that are different from traditional patterns, especially in the form of gending. The creation method in this composition uses Alma W Hawkins' concept, namely exploration, improvisation, and composition. The arrangement of the source of the work uses Western music techniques and harmonized karawitan. Misindhandhang is a karawitan composition work that is not bound by the form of gending, both gatra and chotomic beating. Misindhandhang is the name of a karawitan composition; this name is an acronym from the word Mi=Mijil, Si=Sinom, and Dhandhang comes from the word Dhandhanggula. All three are the names of pupuh sekar Macapat. These three sekar macapat became the primary material, which was then worked on and processed, and finally, works were produced in a new form. The creation of the composition Misindhandhang is intended to open the perception that traditional arts, especially sekar macapat,  can be worked on, developed and given different variations from the original to adapt to the changing times. Misindhandhang's compositional work takes the theme of the phases of human life from birth to youth and adulthood. This research produces new works in the realm of tradition. This work processes the source of the existing work to be different from the original tradition. This process resulted in a karawitan composition work entitled Misindhandhang, with a vocal karawitan presentation with a new form and melody, unlike the original macapat song.  Although the tune is the same, namely the slendro barrel, after processing, it is worked on based on the technique used by the author, resulting in a slendro barrel song like the nuances of a Chinese song. This research concludes that the Javanese tradition is a source of creativity when creating new works.